Efektivitas Penggunaan Media Web Genially Berbasis Model E-Learning dengan Tema Zakat dalam Islam - Sufia, Neng; Vebriyanto, Rian (Borneo Journal of Islamic Education, 2024)
Abstract Learning media is one of the most important components in the teaching and learning process. Therefore, the researcher intends to develop a web-based learning media using Genially with an e-learning model on the theme "Zakat in Islam" for senior high school level at MAN 1 Plus Keterampilan Bengkalis. The methodology used in this research is Research and Development (R&D), involving 30 teachers and 50 students from class X. Data collection was conducted directly by the researcher by explaining the Genially media and then asking respondents to answer questions and assess the quality of the media. The data obtained were analyzed using descriptive analysis. The research findings indicate that the design, interactivity, and material relevance components, as assessed by the teachers, fall into the "Very Good" category, while the average score of students is 4.7 on a 5-point scale, also categorized as "Very Good." Therefore, it can be concluded that the Genially-based e-learning media has very good quality according to the evaluations of both teachers and students. Thus, this media can be used as an effective alternative in teaching Islamic Religious Education, particularly on the topic of zakat. Keywords: Genially Media, Development, Islamic Religious Education, Zakat Abstrak Media pembelajaran merupakan salah satu komponen yang paling penting dalam proses belajar mengajar. Untuk itu, peneliti ingin mengembangkan media pembelajaran berbasis web Genially menggunakan model e-learning dengan tema "Zakat dalam Islam" untuk tingkat SMA di MAN 1 Plus Keterampilan Bengkalis. Metodologi yang digunakan dalam penelitian ini adalah Research and Development (R&D) dengan melibatkan 30 orang guru dan siswa kelas X sebanyak 50 orang. Proses pengambilan data dilakukan secara langsung oleh peneliti dengan menjelaskan media Genially, kemudian meminta responden untuk menjawab pertanyaan dan menilai kualitas media tersebut. Data yang diperoleh dianalisis menggunakan analisis deskriptif. Hasil penelitian menunjukkan bahwa nilai komponen desain, interaktivitas, dan relevansi materi yang dinilai oleh guru berada dalam kategori "Sangat Setuju", sedangkan nilai rata-rata siswa sebesar 4,7 dari skala 5 dengan kategori "Sangat Setuju". Maka, dapat disimpulkan bahwa media Genially berbasis model e-learning memiliki kualitas sangat baik menurut penilaian guru dan siswa. Jadi, media ini dapat digunakan sebagai alternatif yang efektif dalam pembelajaran Pendidikan Agama Islam, khususnya pada materi zakat. Kata Kunci: Media Genially, Pengembangan, Pendidikan Agama Islam, Zakat